Deep Imaging to Dissect Microvascular Contributions to White Matter Degeneration in Rodent Models of Dementia. Issue 5 (25th April 2023) - Stamenkovic, Stefan; Li, Yuandong; Waters, Jack; Shih, Andy
Abstract : The increasing socio-economic burden of Alzheimer disease (AD) and AD-related dementias has created a pressing need to define targets for therapeutic intervention. Deficits in cerebral blood flow and neurovascular function have emerged as early contributors to disease progression. However, the cause, progression, and consequence of small vessel disease in AD/AD-related dementias remains poorly understood, making therapeutic targets difficult to pinpoint. Animal models that recapitulate features of AD/AD-related dementias may provide mechanistic insight because microvascular pathology can be studied as it develops in vivo. Recent advances in in vivo optical and ultrasound-based imaging of the rodent brain facilitate this goal by providing access to deeper brain structures, including white matter and hippocampus, which are more vulnerable to injury during cerebrovascular disease. Here, we highlight these novel imaging approaches and discuss their potential for improving our understanding of vascular contributions to AD/AD-related dementias.